Change the culture, change the game : the breakthrough strategy for energizing your organization and creating accountability for results - Connors, Roger; Smith, Tom (Thomas A.) (New York : Portfolio Penguin, 2011)
Demonstrates how professional leaders can enable record-breaking results by creating a people-centric organizational culture.
Creating a culture of accountability -- Defining the results that guide the change -- Taking action that produces results -- Identifying the beliefs that generate the right actions -- Providing experiences that instill the right beliefs -- Aligning a culture for rapid progress -- Applying the three culture management tools -- Mastering the three culture change leadership skills -- Integrating the culture change -- Enrolling the entire organization in the change.
Includes index.
Keywords: Organizational behavior; Corporate culture; Responsibility; Management